The Implications of Political Killings in Modern-Day Thailand - Anderson, Benedict (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Political killing, as with so much else in modern Thai history, assumed a new character under the regime of Field Marshall Sarit Thanarat. One could plausibly argue that under his rule the range of possible victims of political murder greatly expanded outwards and downwards, while the killer became, more definite than ever before, the state and its apparatus.